2015
DOI: 10.1128/mbio.00589-15
|View full text |Cite
|
Sign up to set email alerts
|

Penile Microbiota and Female Partner Bacterial Vaginosis in Rakai, Uganda

Abstract: Bacterial vaginosis (BV) is a common vaginal bacterial imbalance associated with risk for HIV and poor gynecologic and obstetric outcomes. Male circumcision reduces BV-associated bacteria on the penis and decreases BV in female partners, but the link between penile microbiota and female partner BV is not well understood. We tested the hypothesis that having a female partner with BV increases BV-associated bacteria in uncircumcised men. We characterized penile microbiota composition and density (i.e., the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 52 publications
7
116
1
6
Order By: Relevance
“…Th17 cells are essential in the defense against bacterial infections [78, 79], and colonization by pathogenic bacteria may increase HIV susceptibility by increasing Th17 cell density [50]. We have previously found that uncircumcised men are more likely to have BV-associated anaerobic bacteria in their sub-preputial space [80], and that circumcision gradually reduces both the total bacterial load and the abundance of these anaerobes [32]. Of note, while anaerobe abundance decreased rapidly within 6 months post-circumcision, it continued to decline for up to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are essential in the defense against bacterial infections [78, 79], and colonization by pathogenic bacteria may increase HIV susceptibility by increasing Th17 cell density [50]. We have previously found that uncircumcised men are more likely to have BV-associated anaerobic bacteria in their sub-preputial space [80], and that circumcision gradually reduces both the total bacterial load and the abundance of these anaerobes [32]. Of note, while anaerobe abundance decreased rapidly within 6 months post-circumcision, it continued to decline for up to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study undertaken with 35 Australian women with recurrent BV supported these findings, with the majority reporting BV onset had been triggered by sexual contact [20]. Microbiological data has also shown evidence of male-carriage of BV associated bacteria (BVAB), with uncircumcised male partners of females with BV showing a higher prevalence of BVAB than male partners of women without BV [21]. Concordant with this is evidence to show male circumcision is associated with a significant reduction of BVAB in men [22,23] and a reduced risk of BV in women [24].…”
Section: Introductionmentioning
confidence: 88%
“…Monogamous heterosexual couples develop complementary microbiomes 198, 199 which would suggest that the highest risk to infection of either partner through sexual contact would be in the early stages of a relationship, and that the risk to an individual would be related to the numbers of sexual partners, some of whom might be asymptomatic carriers of pathogenic organisms 200202 .…”
Section: The Three Phases Of Crohn’s Diseasementioning
confidence: 99%